Short communicationInterleukin-6 serum concentration in patients with impaired growth hormone secretion - Biernacka, Anna; Dobaczewski, Marcin; Ławnicka, Hanna; Kunert-Radek, Jolanta (Archives of Medical Science, 2005)
There is a growing number of studies which have revealed that the growth hormone (GH) plays a role in regulation of systemic inflammatory response. Interleukin-6 (IL-6) is a well established pro-inflammatory, proangiogenic and adipocyte expressed cytokine that is also involved in pituitary tumors pathophysiology. In this study, using commercially available kits, we aimed to determine serum concentrations of IL-6, GH and IGF-1 in the following groups of age and sex matched patients expressing impaired growth hormone secretion: patients with active acromegaly (n=11), patients cured from acromegaly (n=14), patients exhibiting growth hormone deficiency (GHD) induced by pituitary tumors (n=12), patients with GHD unrelated to pituitary tumors (n=10) and control group of healthy volunteers (n=15). Concentrations of IL-6 were significantly higher in both GHD groups with reference to controls. Acromegalic patients revealed comparable to healthy subjects IL-6 concentrations. Using segmental regression applied to the group combined of all patients (n=62), a cut off point for GH=2.27 ng/ml was determined below which a negative correlation with IL-6 was confirmed (r=-0.56, p<0.048). Multiple regression failed to reveal any correlation between IL-6 and IGF-1/BMI in groups of patients irrespective of the GH concentration threshold. Taken together, we conclude that GHD in adults is accompanied by increased serum concentrations of IL-6. Nevertheless, neither adipocytes nor pituitary adenoma cells are the major source of IL-6 in these patients. Lack of correlation of IL-6 with IGF-1 suggests the direct impact of low GH concentrations in IL-6 induction. Noteworthy, increased IL-6 concentrations can be secondary to the atherosclerotic process augmented by GHD via mechanisms which require further investigations.